Clinical characteristics and predictors of mortality among COVID-19 patients in Saudi Arabia - Olayan Albalawi; Yousef Alharbi; Mohsen Bakouri; Abdulrahman Alqahtani; Thamer Alanazi; Abdullah Z. Almutairi; Bandar Alosaimi; Ayman Mubarak; Ranjay K. Choudhary; Wael Alturaiki (Elsevier, 2021)
Background: The new coronavirus disease (COVID-19) has caused more than 1.8 million deaths, with a fatality rate of 2.5% in more than 200 countries as of January 4, 2021. Analysis of COVID-19 clinical features can help predict disease severity and risk of mortality, early identification of high-risk patients, and provide knowledge to inform clinical interventions. Objective: The purpose of this study is to investigate the clinical characteristics and possible predictors associated with mortality in patients with COVID-19 admitted to King Fahad (KFH), Ohood, and Miqat hospitals in Madina, Saudi Arabia. Methods: This retrospective observational study to investigate the clinical characteristic and possible predictors associated with mortality for those 119 mild, moderate, or critically ill patients confirmed by laboratory results to have COVID-19 who were admitted to three hospitals in Madina, Saudi Arabia, from March 25, 2020, to July 30, 2020. Data were collected from December 1, 2020, to December 14, 2020. Results: Of the 119 patients included in the study, the mean age was 54.2 (±15.7) years, with 78.2% survivors and 21.8% non-survivors. The demographic analysis indicated that the likelihood of mortality for patients in the older age group (i.e., ≥65 years) was five times higher than those in the younger age group (OR = 5.34, 95% CI 1.71-16.68, p = 0.004). The results also indicated those patients who admitted to the intensive care unit (ICU) was approximately seven times higher odds of mortality compare with those who were not admitted (OR = 6.48, 95% CI 2.52-16.63, p < 0.001). In addition, six laboratory parameters were positively associated with the odds of mortality: white blood cell count (OR = 1.11, 95% CI 1.02-1.21, p = 0.018), neutrophil (OR = 1.11, 95% CI 1.02-1.22, p = 0.020), creatine kinase myocardial band (OR = 1.02, 95% CI 1.00-1.03, p = 0.030), C-reactive protein (OR = 1.01, 95% CI 1.00-1.01, p = 0.002), urea (OR = 1.06, 95% CI 1.01-1.11, p = 0.026), and lactate dehydrogenase (OR = 1.00, 95% CI 1.00-1.01, p = 0.020). Conclusions: In this cohort, COVID-19 patients within the older age group (≥65 years) admitted to the ICU with increased C-reactive protein levels in particular, were associated with increased odds of mortality. Further clinical observations are warranted to support these findings and enhance the mapping and control of this pandemic.